2019
DOI: 10.1080/02670844.2018.1512233
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviour of textured titanium under abrasive wear

Abstract: In order to improve the tribological behaviour of titanium used in aerospace exploration. Dimple textures were prepared on a commercial pure titanium grade 2 (TA2) surface by laser surface texturing. Tribological behaviour of the textured TA2 was investigated under two kinds of simulated lunar soil particles in dry sliding contact. The tribological mechanisms were analysed using NanoMap-D 3D surface profilometer, scanning electron microscope and energy-dispersive spectroscopy. An orthogonal analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that the friction and wear of the materials can be effectively reduced by laser surface texture under different conditions [12][13][14]. Li et al [15] studied the effect of dimple textures on tribological properties of TA2 titanium under simulated lunar soil particles in dry sliding contact. The results showed that the textured surface exhibited a better tribological performance under the small particle condition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the friction and wear of the materials can be effectively reduced by laser surface texture under different conditions [12][13][14]. Li et al [15] studied the effect of dimple textures on tribological properties of TA2 titanium under simulated lunar soil particles in dry sliding contact. The results showed that the textured surface exhibited a better tribological performance under the small particle condition.…”
Section: Introductionmentioning
confidence: 99%
“…Many preliminary studies of boriding pure Ti have been performed, but few investigated different boriding temperatures [14][15][16][17][18]. Kara et al reported that boriding titanium at 950 • C substantially increases its wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Etsion’s studies indicated that the LST enhanced hydrodynamic and hydrostatic lubrication of mechanical seals analytically and experimentally, and there was a significant improvement in the load capacity, anti-wear and friction coefficient, and a substantial reduction in wear and surface damage in comparison with untextured surfaces [10,11]. Li’s study also indicated that the textured titanium surface exhibited better anti-friction and anti-wear performance under the small particle wearing condition compared with that under the large particle [12].…”
Section: Introductionmentioning
confidence: 99%